Comorbidity Matters: Social Visual Attention in a Comparative Study of Autism Spectrum Disorder, Attention-Deficit/Hyperactivity Disorder and Their Comorbidity - Ioannou, Chara; Seernani, Divya; Stefanou, Maria Elena; Riedel, Andreas; Tebartz van Elst, Ludger; Smyrnis, Nikolaos; Fleischhaker, Christian; Biscaldi-Schaefer, Monica; Boccignone, Giuseppe; Klein, Christoph (Frontiers in Psychiatry, 2020)
Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) represent two common neurodevelopmental disorders with considerable co-occurrence. Their comorbidity (ASD+ADHD) has been included in the latest diagnostic guidelines (DSM-V, 2013). The present study focuses on social visual attention that i) is a main aspect of social attention reflecting social cognition and ii) its atypicalities have been suggested as a potential biomarker for ASD. Considering the possible shared background of both disorders and their comorbidity, it is important to compare such traits directly. Here, 73 children and adolescents paired for age and IQ diagnosed with ASD (N=12), ADHD (N=21), comorbid ASD+ADHD (N=15), and “typically developing” (TD) controls (N=25), were shown static real-life social scenes while their gaze movements were recorded with eye-tracking. Scenes with two levels of social complexity were presented: low complexity (one person depicted) and high (four interacting individuals). Gaze fixation variables were investigated. Fixation duration on faces was significantly reduced only in ASD+ADHD which also required longer time to fixate all faces at least once. Fixation duration on faces in ASD was reduced, compared to TD, only when looking at scenes with high vs. low social complexity. ADHD individuals did not differ from TD. Concluding, the observed alterations of social visual attention support the existence of possible dysfunctional particularities differentiating ASD, ADHD and ASD+ADHD, which can be revealed with the new method of eye-tracking technique. The objective gaze measurements provided contribute to development of biomarkers enabling early diagnosis, amelioration of care and further interventions specified for each group.